(untitled) (Modern education and development, 2025)
This article explores effective strategies for teaching preschool children, emphasizing play-based learning, multi-sensory activities, social interaction, and routine establishment. It highlights the importance of adaptation in preschool education, including individualized learning approaches, cultural considerations, and support for children with special needs. The role of teachers and parental involvement in early childhood development is also discussed. The article is supported by relevant theories and research, ensuring a comprehensive and evidence-based approach to preschool teaching.